The Effectiveness Of 5E’s Learning According To The Constructivist Theory In The Acquisition Of Quranic Rhetorical Systems Toward Non-Arabic Speakers/ فاعلية دورة التعلم الخماسية وفق النظرية البنائية في اكتساب مهارات التذوق البلاغي للنظم القرآني لدى الناطقين بغير العربية - A-eshah Waemamah; Siti Salwa Binti Mohd Noor; Abdul Wahid Bin Salleh; Haniah Haniah (Ijaz Arabi Journal of Arabic Learning, 2023)
This study aimed to measure the effectiveness of the 5E’s learning strategy according to the constructivist theory in the acquiring Rhetorical Taste of Quranic systems toward Non-Arabic speakers from the Department of Arabic Language at Princess Naradiwas University -Thailand. This study used an analytical-descriptive approach to determine the rhetorical taste skills of the Quranic systems. It used a semi-experimental method of the one-group design for test 5E’s learning strategy on the study group, which consisted of (24) students. To achieve the aim of this study, it designed a list of the rhetorical taste skills of the Quranic systems, then prepared a program based on the 5E’s learning strategy for the Semantics course and a rhetorical taste test. The study reached to identify 28 skills from five primary skills for the Qur’anic rhetoric. There is a statistically significant difference between the students' mean pre- and post-measurement scores. The difference was statistically significant in the (13) skills. However, the difference was not statistically significant in (15) skills. The study concluded with many recommendations and suggestions.